Expression characteristics of AXL and YAP in non-small cell lung cancer and prognostic importance - Zhao, Chun (Int J Clin Exp Pathol, 2018)
Lung cancer has some of the highest morbidity and mortality. It is an urgent task to illuminate the exact mechanism of tumorigenesis of lung cancer. Previous studies suggested that receptor tyrosine kinase family member AXL and Hippo signal pathway co-activator YAP may be important signal molecules in tumorigenesis. In this paper we detect AXL and YAP expression in 81 non-small cell lung cancer cases that received surgery, and we discuss the relationship between the expression of AXL and YAP and tissue type, pathological staging, and degree of differentiation. We found that in NSCLC tissues AXL(Low)YAP(Low) was 29.63%, AXL(High)YAP(Low) was 13.58%, AXL(Low)YAP(High) was 25.93% and AXL(High)YAP(High) was 30.86%. The expression pattern of AXL and YAP was related to the degree of differentiation, T stage and pathological stage. Based on clinical follow-up data, we assessed the prognostic significance of AXL and YAP combined, with respect to recurrence and long-term survival. NSCLC tended to show AXL and YAP high expression, and high expression of AXL and YAP in NSCLC tissues suggested worse prognosis. Combined detection of AXL and YAP may be a new index to predict NSCLC patients’ prognosis.